Parents' Responsibilities Towards Child Support Owed From The Perspective Of Khi And Law - Guvo Deswarth Purba; Febry Anggina Nasution (AT-TAFAHUM: Journal of Law, 2019)
This study aims to investigate and analyze the legal responsibility of parents for child support debts from the perspective of the Islamic Law Code (KHI) and the Law. In this study, the researcher reviewed the definition and concept of support, the legal responsibility of parents in providing support to children, the period of parental responsibility, the economic capacity of parents, and the legal consequences that may be faced by parents who do not fulfill their support obligations. This study uses a document analysis method with reference to relevant articles in the KHI and the Law. The researcher also involved a comparative study between the perspectives of Islamic law and positive law to gain a more comprehensive understanding of the legal responsibility of parents for child support debts. The results of this study are expected to provide a deeper understanding of the legal responsibility of parents in providing support to children who are in debt. In addition, this study is also expected to provide guidance for legal practitioners, family experts, and the general public in understanding and handling cases related to the legal responsibility of parents for child support debts.